Celebrating identity: History teaching and commemorations in Primary Education - Toro-Pérez, Jose Jaime; Parra Monserrat, David (Revista Complutense de Educación, 2022)
This article aims to analyze the type of citizenship and collective identities schools generate through the educational treatment of historical-cultural aspects. For this, not only the contents worked in class are attended, but also practices such as school celebrations that contribute in the same way to socialization in a culture and common values. In this sense, the research focuses on the treatment of the Middle Ages (especially the Christian conquest) and its identity uses in Valencian schools based on a structured analysis of different aspects: curriculum, textbooks, daily practices and, particularly for this case, the yearly school celebration, on October 9th, of the conquest of Valencia- an event which has given rise to the Day of the Valencian Community. To this end, the study is considered from both a qualitative and a comparative approach, since data from two different educational laws (LOE and LOMCE) have been collected with the aim of tracking changes and continuities. Firstly, we review the curriculum of History for the 5th year of Primary Education -when the Middle Ages are studied-, in order to later examine its development in textbooks. Secondly, for analyze specific classroom practices and students’ learning, we examine 90 questionnaires answered by teachers from 68 schools and 65 historical narratives of fifth grade students. The results point out that these contents are generally treated trivially and thoughtlessly, showing the survival of traditional identity discourses and a poor education in historical and civic skills.
Keywords: primary school; history; curriculum; textbook; cultural identity